Consumo y costo de ceftriaxona 1g en el servicio de medicina interna “6C” del Hospital Nacional Edgardo Rebagliati Martins, enero - diciembre del 2007 - Guillén Ortiz, Flor de María (2008)
This Labour Research, is a descriptive study, cross-sectional whose and retrospective, overall objective is determine consumption and cost of Ceftriaxone 1g in the Internal Medicine Department "6C". The sample universe was composed of patients hospitalized in the Internal Medicine Department attended from 01 January 2007 to December 31, 2007. The cost and consumption data were drawn from the database management system Hospital pharmacy unit dose hospital. Consumption of Ceftriaxone 1g in the Internal Medicine Department of National Hospital Edgardo Rebagliati Martins was: DDD/100 16.75 beds per day on average and had a statistically significant tendency to increase. The annual expenditure of imipenem / cilastatin in the Internal Medicine Department of National Hospital Edgardo Rebagliati Martins was: S /. 11 562.08